The Effect of Rewards on Employee Performance with Employee Engagement as an Intervening Variable in Indonesian Pharmaceutical Companies - Nurmalita Dwiyanti; Nidya Dudija (AIBPM Publisher, 2019)
Employee performance has a major contribution to organizational effectiveness. There are several factors that possibly improve employee performance including rewards and employee engagement. The purpose of this study is to determine the effect of financial and non-financial rewards on employee performance with employee engagement as an intervening variable. This study conducted on leading pharmaceutical companies in Indonesia. Data collection using questionnaires, the distribution using disproportionate stratified random sampling technique. Data analysis uses path analysis. The results show that both forms of rewards and employee engagement significantly influence employee performance simultaneously and partially. There is an influence of employee engagement in mediating the relationship of financial rewards on employee performance as well as the relationship between non-financial reward on employee performance.